Effect of repetitive education on cognitive-social factors among type 2 diabetic patients - Erkoc, Arzu; Tan, Mehtap (International Journal of Research in Medical Sciences, 2017)
Background: Psychological, cognitive and social factors are also effective in helping the diabetes patient show behavioral changes in terms of the treatment process. The purpose of this study was to examine the effect of repetitive education on cognitive-social factors and metabolic control variables among patients with type 2 diabetes (T2DM). Methods: The study was conducted with one group using the same test at pre-determined times. 62 outpatients with T2DM were recruited for this study. The data was collected using a Patient Information Form that was prepared by the researchers, the Turkish multidimensional diabetes questionnaire, and the metabolic control follow-up form. The data was analyzed using SPSS 19 and descriptive statistics (Kolmogorov-Smirnov Test, Paired t Test, and Wilcoxon Signed-Rank Test). Results: While there was a statistically significant difference between the mean scores of interference, severity, positive reinforcing behaviors, outcome expectancies before and after the diabetes education (p˂0.05), a statistically significant difference was not found between mean values of fasting and random plasma glucose, HbA1C, HDL, LDL, triglyceride, waist circumference and body mass index (p˃0.05). Conclusions: Repetitive diabetes education provided to patients with T2DM positively affected other cognitive-social factors except for social support and self-efficacy, but did not affect metabolic control variables except for blood pressure.